Tinjauan Yuridis Pelaksanaan Perjanjian Sewa Menyewa Rumah Toko Di Wilayah Semarang Barat - Arif Rifqi Muslim; Achmad Busro (Notarius, 2022)
AbstractImplementation of lease agreements is often a problem in shophouse rentals. The focus of the problem in this study is How the Legal Review of the Implementation of the Rental Agreement for Shop Houses (ruko) in the City of Semarang, How the Legal Protection Forms the Rental-Renting Agreement for Shop Houses (ruko) The method used in this research is an empirical juridical approach, namely research that utilizes the laws of the environment in a real sense and examines how it works in the community which aims to understand what is done by research subjects and in a descriptive way in the form of words and language by utilizing various books. -scientific books. The results of this study indicate that the implementation of the lease agreement must go through the stages starting with the pre-agreement stage, the stage of the Agreement Preparation, the post-signing of the agreement. The form of legal protection The lease agreement is regulated in chapter VII of Book III of the Civil Code entitled "About Leasing" which includes articles 1548 to 1600 of the Civil CodeKeywords: agreements; rent; shop house.AbstrakPelaksanaan perjanjian sewa sering menjadi masalah dalam persewaan ruko. Fokus permasalahan dalam penelitian ini adalah Bagaimana Tinjauan Hukum Pelaksanaan Perjanjian Sewa Ruko (ruko) di Kota Semarang, Bagaimana Perlindungan Hukum Bentuk Perjanjian Sewa-Menyewa Ruko (ruko) Metodenya Yang digunakan dalam artikel ini adalah pendekatan yuridis empiris, yaitu penelitian yang memanfaatkan hukum lingkungan dalam arti yang sebenarnya dan menelaah cara kerjanya dalam masyarakat yang bertujuan untuk memahami apa yang dilakukan oleh subjek penelitian dan secara deskriptif berupa kata dan bahasa dengan memanfaatkan berbagai buku. -buku ilmiah. Hasil penelitian ini menunjukkan bahwa pelaksanaan perjanjian sewa harus melalui tahapan yang dimulai dari tahap pra perjanjian, tahap pembuatan perjanjian, hingga pasca penandatanganan perjanjian. Bentuk Perlindungan Hukum Perjanjian Sewa diatur dalam Bab VII Buku III KUH Perdata yang berjudul “Tentang Sewa” yang memuat pasal 1548 sampai dengan 1600 KUH Perdata.Kata kunci : perjanjian; menyewa; rumah toko